CORPORATE FINANCIAL COMMUNICATION: How Financial Performances Affect the Perceived-Value of a Company - Purama, Tegar Aafanie (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
Financial communication is how financial performance can be 'read' by the audience and form a certain perception regarding the value of an object, in this context, it can be a company, community, organization, institution, or even an individual. This study aims to determine the effect of Debt to Assets Ratio (DAR), Dividend Payout Ratio (DPR), Return On assets (ROA) and Net Profit Margin (NPM), Against Dividend Payout Ratio (DPR) on perceived-value of companies listed on the Stock Exchange Indonesian Securities 2015-2018. This research uses a quantitative approach by collecting secondary data obtained from IDX. The population in this study is the food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The sampling method is purposive, by determining sample with some specific considerations or with special selection aimed at making the data obtained more representative. The analytical tools used include autocorrelation and reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, f, t-test, and R2 test. To cite this article (7th APA style): Purama, T. A. (2022). Corporate Financial Communication: How Financial Performances Affect the Perceived-Value of a Company. Journal Communication Spectrum, 12(1), 49-56. https://doi.org/10.36782/jcs.v12i1.2000